Minimum Spanning Tree Algorithm for Skin Cancer Image Object Detection - هند رستم محمد (College of Education for Women, 2019)
This paper proposes a new method Object Detection in Skin Cancer Image, the minimum spanning tree Detection descriptor (MST). This ObjectDetection descriptor builds on the structure of the minimum spanning tree constructed on the targettraining set of Skin Cancer Images only. The Skin Cancer Image Detection of test objects relies on their distances to the closest edge of thattree. Our experimentsshow that the Minimum Spanning Tree (MST) performs especially well in case of Fogginessimage problems and in highNoisespaces for Skin Cancer Image. The proposed method of Object Detection Skin Cancer Image wasimplemented and tested on different Skin Cancer Images. We obtained very good results . The experiment showed that the proposedmethod obtained very good results but it requires more testing on different types of Skin Cancer Images.